Conditional Ror1 knockout reveals crucial involvement in lung adenocarcinoma development and identifies novel HIF‐1α regulator - Isomura, Hisanori; Taguchi, Ayumu; Kajino, Taisuke; Asai, Naoya; Nakatochi, Masahiro; Kato, Seiichi; Suzuki, Keiko; Yanagisawa, Kiyoshi; Suzuki, Motoshi; Fujishita, Teruaki; Yamaguchi, Tomoya; Takahashi, Masahide; et al. (Cancer science, 2021)
We previously reported that ROR1 is a crucial downstream gene for the TTF‐1/NKX2‐1 lineage‐survival oncogene in lung adenocarcinoma, while others have found altered expression of ROR1 in multiple cancer types. Accumulated evidence therefore indicates ROR1 as an attractive molecular target, though it has yet to be determined whether targeting Ror1 can inhibit tumor development and growth in vivo. To this end, genetically engineered mice carrying homozygously floxed Ror1 alleles and an SP‐C promoter–driven human mutant EGFR transgene were generated. Ror1 ablation resulted in marked retardation of tumor development and progression in association with reduced malignant characteristics and significantly better survival. Interestingly, gene set enrichment analysis identified a hypoxia‐induced gene set (HALLMARK_HYPOXIA) as most significantly downregulated by Ror1 ablation in vivo, which led to findings showing that ROR1 knockdown diminished HIF‐1α expression under normoxia and clearly hampered HIF‐1α induction in response to hypoxia in human lung adenocarcinoma cell lines. The present results directly demonstrate the importance of Ror1 for in vivo development and progression of lung adenocarcinoma, and also identify Ror1 as a novel regulator of Hif‐1α. Thus, a future study aimed at the development of a novel therapeutic targeting ROR1 for treatment of solid tumors such as seen in lung cancer, which are frequently accompanied with a hypoxic tumor microenvironment, is warranted. Conditional Ror1 knockout mice carrying a human mutant EGFR transgene were established in the present study. Experiments with that animal model clearly demonstrated that Ror1 has crucial involvement in lung adenocarcinoma development and growth in vivo.